SITUATION OF ORGANIZATION, HUMAN RESOURCE AND STRUCTURE OF 54 PROVINCIAL CENTERS FOR DISEASE CONTROL (Vietnam Journal of Community Medicine, 2024)
Introduction: Provincial Centers for disease control (CDCs), public health facilities, have beenformed based on merging provincial centers in preventive medicine areas since 2017. Staffing normsand the structure of the CDCs has not beenregulated.Objective: To describe the situation of human resources, organization and structure of CDCs in2019-2020.Methods: Cross-sectional study, quantitative information was obtained from the statistical formprovided by 54 CDCs.Results: Out of 54 CDCs, 64.8% have 12 or more technical divisions and 85.0% have enoughthree administrative units; 98.2% met the norm 65.0% of staff working in medical and non-medicalspecialties positions; 16.4% have the proportion of doctor/preventive doctor ≥ 30%Conclusions: The number of people working in CDCs having been merged from 5 or more centerswas proportional to the size of the province’s population. The study provides practical evidence onCDC’s human resources and its structure to propose appropriate staffing norms proportional to theprovinces’ population size and structure of CDCs.
Keywords: Centers for disease control (CDC), staffing norms, human resource, structure, organization, medical specialty.